(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Introduction : The incidence and number of tuberculosis (TB) cases have been increased dramatically all over the world. It is a major public health problem in Bangladesh too. Case Summary : A 5-months old male infant, immunized as per EPI schedule, 3rd issue of a nonconsanguinous parents residence at downtown, Dhaka from a poor socioeconomic background was admitted into the Paediatrics ward, Bangladesh Medical College Hospital on 11th March 2004 with fever for 1 month, dry cough for 21 days, loose motion and vomiting for 14 days. He was weaned from breast milk at 3 months of his age and there was gross malfeeding history. BCG vaccine was given at 6 weeks. His mother had also been suffering from recurrent febrile illnesses and weight loss for many months. Baby was looking ill but conscious, mildly pale, afebrile with no dyspnoea. Z score of wt/age, lth/age, wt/lth and OFC were -2.9, -3.5, -0.3 and -0.3 respectively. Fontanel was open and normal. There was no lymphadenopathy and BCG mark was present. Breath sound was vesicular with fine crepitation on right lung. He was treated initially as septicemia by combined parenteral antibiotics. But response was not satisfactory. Lab data yielded raised ESR, eosinophillia, pyuria and haematuria with sterile culture. Chest X ray was abnormal. Mantoux Test (MT) was found strongly positive (18mm/72hrs.). Other family members were immediately screened for TB and all revealed positive. Complete Blood Count, MT and Chest X ray were chosen as screening methods for them. We treated with anti tubercular therapy to all of them including baby. We also corrected the feeding practice of the patient and kept in close monitoring. He showed remarkable clinical improvement with weight gaining. We discharged him as disseminated tuberculosis with having pulmonary tuberculosis among all other family members and advised for follow up. They all were cured. At present, they are healthy and baby is now 4 years of age with good physical and mental growth. Conclusion : TB can mimic everything. A high index of suspicion by the clinician is essential for early diagnosis. Message: Family members of affected child must be screened for active TB Keywords : Tuberculosis; Tuberculosis in infant; Pan family tuberculosis. DOI: 10.3126/saarctb.v6i2.3056 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (2) 38-42